2010
DOI: 10.1007/s10552-010-9677-4
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and endogenous sex hormones in postmenopausal women: to what extent are observed associations confounded or modified by BMI?

Abstract: Sports activities may lead to lower levels of estrone and testosterone in postmenopausal women. While effects on estrone and free testosterone seem to be largely mediated by BMI, effects on total testosterone appear to be mainly independent of BMI. The BMI-independent effects on these hormones (especially on total testosterone) could at least partly explain why physical activity has been frequently reported to be preventive for postmenopausal breast cancer, even after accounting for BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 48 publications
0
27
0
1
Order By: Relevance
“…60 Only sports activities such as fitness training, swimming, or gymnastics appear to reduce levels of estrone and testosterone, which are hormones related to breast cancer risk in postmenopausal women. 61 There is no relationship between these hormones and leisurely walking or bicycling. 61 In addition, leisurely physical activity has been found to have no association with coronary calcification in early postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Only sports activities such as fitness training, swimming, or gymnastics appear to reduce levels of estrone and testosterone, which are hormones related to breast cancer risk in postmenopausal women. 61 There is no relationship between these hormones and leisurely walking or bicycling. 61 In addition, leisurely physical activity has been found to have no association with coronary calcification in early postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…61 There is no relationship between these hormones and leisurely walking or bicycling. 61 In addition, leisurely physical activity has been found to have no association with coronary calcification in early postmenopausal women. 62 Finally, this study did not measure levels of oxidative stress and cannot directly investigate the role of oxidative stress as a mediator between telomere length in PBMCs and habitual exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically for steroid hormonal pathways, epidemiologic studies have found direct associations between postmenopausal endogenous levels of steroid hormones and breast cancer (33). Postmenopausal women who are physically active in comparison with inactive women may have lower concentrations of serum estrone, estradiol, and androgens (34,35) and higher sex hormone-binding globulin (36). Furthermore, substantial epidemiologic, clinical, and experimental evidence has clearly established a late-stage growth promoting effect of estrogens (37), which would be in line with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Among adults, an association between higher physical activity and lower estrogens and androgens has been observed in premenopausal [25] and postmenopausal [26][27][28] women. In men, a few studies have reported a positive association [29] or no association [30] between physical activity and testosterone.…”
Section: Discussionmentioning
confidence: 99%